KORELASI KEPUASAN KERJA DAN MOTIVASI BERPRESTASI DENGAN KINERJA GURU DI SEKOLAH DASAR KINDERFIELD - Fredy Hidayat; Manahan P. Tampubolon; Hotmaulina Sihotang (Jurnal Manajemen Pendidikan, 2018)
Fredy Hidayat.Cs. Correlation between Job Satisfaction and Achievement Motivation with Teacher’s Performance in Kinderfield Primary School. Thesis. Magister of Educational Administration/Management Program, Indonesian Christian University, Jakarta, 2018. This research aims to determine the correlation between job satisfaction and achievement motivation with teacher’s performance, with the Job Satisfaction (X1) and Achievement Motivation (X2) as independent variable and Teacher’s Performance (Y) as dependent variable. The research was conducted in 5 centers of Kinderfield Primary School : Cirebon, Bekasi, Sunter, Simprug and Depok . The research population and sample was all teachers who teach in Kinderfield Primary School which totally 100 teachers by using saturation sampling technique. The research instrument was a questionnaire eligible of validity and reliability with Likert model which measures 1-4. Analysis of the data was using simple correlation analysis, multiple correlation and multiple regression at alpha significance level 0.05 by using SPSS 20th version. Based on data analysis, the correlation coefficient between X1 and Y is 0,435 and significant at 0.05 level; the correlation coefficient between X2 and Y is 0,690 and significant at 0.05 level; while the correlation coefficient between X1 and X2 with Y is 0,735 and significant at 0.05 level. Based on regression analysis, the regression equation between X1 and Y is Ý = 72,684 + 0,396 X1, the regression equation between X2 and Y is Ý = 35,882 + 0,966 X2, and the multiple regression equation between X1 and X2 with Y is Ý = 21,636 + 0,241 X1 + 0,864 X2. The results of the research are : 1) there is a positive and significant relationship between job satisfaction and teacher’s performance ; 2) there is a positive and significant relationship between achievement motivation and teacher’s performance, and 3) there is a positive and significant relationship between job satisfaction and achievement motivation simultaneously with teacher’s performance